Observation and characterization of traveling ionospheric disturbances induced by solar eclipse of 20 March 2015 using incoherent scatter radars and GPS networks. (15th September 2019) - Panasenko, Sergii V.; Otsuka, Yuichi; van de Kamp, Max; Chernogor, Leonid F.; Shinbori, Atsuki; Tsugawa, Takuya; Nishioka, Michi
Abstract: We present the results of a comprehensive study of traveling ionospheric disturbances (TIDs) occurring over Europe during the total solar eclipse of 20 March 2015. For detection of wave structures and estimation of TID parameters, two remote sensing techniques were combined: incoherent scatter (IS) radars and European and Finnish dense GPS receiver networks. Similar procedures were applied for processing both IS and GPS data. We developed a new method enabling to analyze TEC data separately in the temporal and spatial domain. For the first time, we produced maps of band-pass filtered TEC variations and reported both large- and medium-scale prevailing TIDs observed during this solar eclipse, both having similar periods of about 50 – 60 min. The downward phase progression indicates that TIDs were induced by atmospheric gravity waves generated at lower altitudes. The variations in IS power attained peak relative amplitudes of 0.22 (22%) at 220 km over Tromsø and of 0.17 (17%) at 200 km over Kharkiv. The vertical phase velocity was about 57 m/s over Tromsø. It increased from 25 to 170 m/s over Kharkiv with altitude increasing from 120 to 310 km. Over Western Europe, large-scale TIDs (LSTIDs) had prevailing north-east direction over the region from 45°to 50°N and 2°W to 8°E. Here, their average horizontal phase velocity V m was 803 ± 281 m∕s and the absolute amplitudes of TEC variations usually do not exceed 0.17 TECU. For this region, we found strong differences in LSTID propagation azimuth between the solar eclipse day and the two adjacent days of 19 and 21 March 2015, used as reference. This most likely indicates that these LSTIDs were directly caused by the solar eclipse through local heating/cooling processes occurring during the passing of the Moon penumbra. Over another region, limited by 44°–50°N and 13°–19°E, the LSTIDs had south-east propagation. Over Finland, the LSTIDs also propagated southeastward having V m = 774 ± 202 m∕s and TEC amplitudes up to 0.6 TECU. A possible evidence of LSTID generation at high latitudes indirectly by this solar eclipse through an excitation of slow magnetosonic waves was experimentally detected. Medium-scale TIDs (MSTIDs) propagated southeastward over both regions having V m values of 144 ± 54 m∕s over Western Europe and of 104 ± 43 m∕s over Finland. Over Northern Europe, the maximum MSTID amplitudes were greater by a factor of 5 compared to those over Western Europe and reached 0.4 TECU. We did not detect a clear difference in MSTID propagation between solar eclipse and reference days. The IS and GPS results are in consistency with each other. The detected TID parameters of predominant periods, relative amplitudes, altitude range and MSTID horizontal propagation direction generally correspond to the results of other studies. Highlights: We have applied a complex approach for TID detection using incoherent scatter radars, dense GPS receiver networks and unified methods. Both large-scale TIDs (LSTIDs) and medium-scale TIDs (MSTIDs) with similar main period of 50–60 min were identified. The downward phase progression points out that TIDs were induced by atmospheric gravity waves generated at lower altitudes. Over Western Europe, LSTIDs have prevailing north-east direction that approximately coincides with the motion of the Moon shadow. Constructed TID maps and animation movies show a very complicated wave field behavior reflecting the propagation features at each location.